The effect of almond intake on anthropometric indices: a systematic review and meta-analysis. Issue 9 (28th August 2020) - Eslampour, Elham; Moodi, Vihan; Asbaghi, Omid; Ghaedi, Ehsan; Shirinbakhshmasoleh, Mina; Hadi, Amir; Miraghajani, Maryam
Abstract : This systematic review and meta-analysis of randomized controlled trials (RCTs) was conducted to summarize the effect of almond intake on anthropometric indices in adult subjects. Abstract : This systematic review and meta-analysis of randomized controlled trials (RCTs) was conducted to summarize the effect of almond intake on anthropometric indices in adult subjects. We searched PubMed, Scopus, ISI Web of Science, Cochrane Library, and Google Scholar databases until January 2020 to identify relevant RCTs. Data were reported as weighted mean differences (WMDs) and standard deviations (SDs) to show the magnitude of effects of almond on body weight (BW), body mass index (BMI), waist circumference (WC), fat mass (FM), and fat-free mass (FFM). Out of 2983 reports, 28 RCTs (37 arms) were eligible for including in our meta-analysis. The pooled results, obtained using a random-effects model, showed that almond intake significantly decreased BW (WMD: −0.38 kg, 95% CI: −0.65, −0.10, p = 0.007, I 2 = 30.5%) and FM (WMD: −0.58 kg, 95% CI: −0.87, −0.28, p < 0.001, I 2 = 4.9%). However, we found no significant effect of almond administration on BMI (WMD: −0.30 kg m −2, 95% CI: −0.67, 0.06, p = 0.101, I 2 = 62.6%), WC (WMD: −0.60 cm, 95% CI: −1.28, 0.06, p = 0.078, I 2 = 0.0%), and FFM (WMD: 0.23 kg, 95% CI: −0.04, 0.50, p = 0.097, I 2 = 49.5%). Overall, the current meta-analysis demonstrated that resveratrol almond intake significantly reduced weight and FM, but did not affect BMI, WC, and FFM. Further studies are still required to confirm our results.